Effects of temperature and soil moisture on gross nitrification and denitrification rates of a Chinese lowland paddy field soil - Tan, Xuezhi; Shao, Dongguo; Gu, Wenquan (Paddy and water environment, 2018)
Alternate wetting and drying (AWD) irrigation is widely adopted to save water in rice production. AWD practice shifts lowland paddy fields from being continuously anaerobic to being alternately anaerobic and aerobic, thus affecting nitrogen (N) transformations in paddy field soils. Using the barometric process separation technique, a large number of soil cores sampled from lowland paddy field soil profiles were measured for gross nitrification and denitrification rates under different temperature and soil moisture conditions. The gross nitrification and denitrification rates vary with rice growth stages and range between 1.18–30.8 and 0.65–13.54 mg N m −3 h −1 , respectively. Results indicate that both gross nitrification and denitrification rates increased with the increase in temperature in all three studied soil layers. Gross nitrification rates significantly decrease with increasing soil moisture while denitrification rates increase, and different soil layers demonstrated different rates of variation to the increase in soil moisture. Gross nitrification rates in the cultivated horizon layer decreased more sharply with the increase in soil moisture. High soil water content is favorable to denitrification of all soil layers.